Determinants of Non-Financial Risk Disclosure: An Empirical Study of Polish Listed Companies in the Context of Directive 2014/95/EU - Łukasz MATUSZAK; Ewa RÓŻAŃSKA (Communications of International Proceedings, 2021)
Purpose: The purpose of this study is to investigate both the extent of non-financial risk disclosure and its determinants in Polish companies subject to the Directive 2014/95/EU. Design/methodology/approach: The sample comprised 71 selected listed companies over 6 years. Content analysis was used to measure the extent of risk-related disclosure. The econometric model was estimated using panel fixed effects. Findings: The extent of non-financial risk disclosure is significantly better than before the implementation of the Directive. Furthermore, we found that the Directive enforcement, company experience in sustainability reporting and company membership in a risky industry are significant determinants of non-financial risk-related disclosure. Originality: Our study enriches the literature on the measurement of the non-financial risk-related disclosure by providing self-constructed non-financial risk disclosure index based on requirements of the Directive 2014/95/EU. It also contributes to the understanding of the role of relevant variables in non-financial risk-related disclosure that has been scarcely investigated.
Keywords: non-financial risk disclosure; risk management disclosure; ESG-related risk disclosure; sustainability risk disclosure; extra-financial risks; Directive 2014/95/EU